A 42 year male presenting with swelling in both parotid regions - Alam, Mohammad Rafiul; Mahmud, Sharfuddin; Rahman, Md Siddiqur; Islam, Md Shaikhul; Dutta, Utpal Kumar; Aich, Mani Lal; Alam, Md Zahedul (Bangladesh Medical Journal, 2016)
A 42 years old male smoker presented with swelling in both parotid regions, 3.5x2.5cm in left & and about 2.5x1.5 cm in right, for 8 months with no pain, fever, dysphagia, dyspnoea, epistaxis or any ear problem. After all necessary investigations, including MRI and FNA, it was diagnosed as Warthin tumor. Warthin`s tumour is a benign tumour of salivary glands affecting mostly parotid gland. Smokers and older individuals are at greater risk of developing Warthin`s tumour. FNA has good accuracy for diagnosing this type of tumour though some literatures show risk of developing sialocutaneous fistula. MRI possesses high specificity and sensitivity for warthin`s tumour. From different available treatment options we chose local excision. Bangladesh Med J. 2015 May; 44 (2): 109-111